ACCURACY OF BODY MASS INDEX BASED ON SELF-REPORT DATA AMONG LAW ENFORCEMENT CADETS - Johnson, Quincy R.; Joyce, Jillian M.; Kukic, Filip; Lockie, Robert G.; Kornhauser, Charles L.; Orr, Robin M.; Dawes, J. Jay (NBP. Nauka, bezbednosti, policija, 2020)
Height and body mass are often self-reported by study participants. However, the accuracy of this data compared to measured values is limited in tactical trainee populations. This study’s purpose was to compare the accuracy of self-reported height and body mass to measured values within a US law enforcement cadet population, and determine how these estimations affected BMI classifications.  METHODS: Self-reported and measured body height and body mass for twenty-six (n=26) male and female cadets (males – age: 31.32 ± 10.04 years; measured height: 178.07 ± 9.87 cm; measured body mass: 92.44 ± 19.37 kg; females – age: 25.67 ± 1.53 years; measured body height: 168.17 ± 4.01 cm; measured body mass: 78.94 ± 11.30 kg) were analyzed. RESULTS: Significant differences between estimated and measured height (p=0.000), body mass (p=0.017), but not BMI (p=0.281) were revealed. CONCLUSION: Self-reported body height and body mass were not accurately reported when compared to measured values. However, reported resulted in accurate BMI classifications.
Keywords: anthropometrics; health assessment; police; obesity.